2016
DOI: 10.1002/chem.201600114
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the “Three‐Finger Pharmacophore” Required for p53–MDM2 Inhibition by Saturation‐Transfer Difference (STD) NMR Initial Growth‐Rates Approach

Abstract: Inhibitors of the p53-MDM2 protein-protein interaction are emerging as a new and validated approach to treating cancer. Herein, we describe the synthesis and inhibitory evaluation of a series of isoquinolin-1-one analogues, and highlight the utility of an initial growth-rates saturation-transfer difference (STD) NMR approach supported by protein-ligand docking to investigate p53-MDM2 inhibition. The approach is illustrated by the study of compound 1, providing key insights into the binding mode of this kind of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…To provide structural details of the binding of these compounds in the p53 binding site, we employed an STD NMR initial growth-rates approach to identify the binding mode and the interactions with the binding grooves of h DM2 and h DMX 2729. Compound 4 was chosen for analysis by STD NMR because of its solubility in aqueous buffer and its relatively weak binding to both h DM2 and h DMX, allowing the binding kinetics to fall within the fast-exchange conditions necessary for STD NMR.…”
Section: Resultsmentioning
confidence: 99%
“…To provide structural details of the binding of these compounds in the p53 binding site, we employed an STD NMR initial growth-rates approach to identify the binding mode and the interactions with the binding grooves of h DM2 and h DMX 2729. Compound 4 was chosen for analysis by STD NMR because of its solubility in aqueous buffer and its relatively weak binding to both h DM2 and h DMX, allowing the binding kinetics to fall within the fast-exchange conditions necessary for STD NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Previous docking studies with different compounds capable to inhibit the MDM2–p53 interaction showed that those compounds are able to mimic the key p53-residues when binding to MDM2 [58,59].…”
Section: Resultsmentioning
confidence: 99%
“…Artefacts can result with measurement of STD at a single saturation time because the accumulated saturation varies with T 1 relaxation rates across the ligand. The problem can be overcome by obtaining initial rates of magnetization transfer derived from saturation buildup curves, 2830 or by CORCEMA-ST calculation of the buildup curves. 31 Collection of multiple saturation time points was precluded here by the rather low stability of the complexes.…”
Section: Introductionmentioning
confidence: 99%